INFORMATION CULTURE OF MASTERS OF SOCIAL PEDAGOGY - Dobroskok, I.I. (Pedagogy of Higher and Secondary Education, 2022)
The article investigates problem of informational culture formation of a future social worker in fessional training process. Main factors which condition the necessity of informational culture formation ture specialist have been defined. The author specifies the notions virtual teaching means and specialists in social pedagogy for professional activity.